2020
DOI: 10.1038/s41598-020-62115-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced purification coupled with biophysical analyses shows cross-β structure as a core building block for Streptococcus mutans functional amyloids

Abstract: Streptococcus mutans is an etiologic agent of human dental caries that forms dental plaque biofilms containing functional amyloids. Three amyloidogenic proteins, P1, WapA, and Smu_63c were previously identified. C123 and AgA are naturally occurring amyloid-forming fragments of P1 and WapA, respectively. We determined that four amyloidophilic dyes, ThT, CDy11, BD-oligo, and MK-H4, differentiate C123, AgA, and Smu_63c amyloid from monomers, but non-specific binding to bacterial cells in the absence of amyloid pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 61 publications
1
32
0
Order By: Relevance
“…TEM visualization of amyloid material induced by mechanical agitation of purified proteins, followed by treatment with proteinase K, revealed a mat-like structure for glycosylated Cnm but a fibrillar morphology for non-glycosylated Cnm and CBD. Mat-like aggregates have been proposed as a more biologically germane form of S. mutans amyloids that represent a supramolecular structure composed of amyloid fibers, monomers, and oligomer intermediates (48) where pure fibers, achieved by proteolytic digestion of S. mutans amyloid-containing mats, are likely only seen in laboratory settings. It has also been shown that the addition of monomeric protein to purified fibrils shifts the morphology of fibrils back to mats (48).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TEM visualization of amyloid material induced by mechanical agitation of purified proteins, followed by treatment with proteinase K, revealed a mat-like structure for glycosylated Cnm but a fibrillar morphology for non-glycosylated Cnm and CBD. Mat-like aggregates have been proposed as a more biologically germane form of S. mutans amyloids that represent a supramolecular structure composed of amyloid fibers, monomers, and oligomer intermediates (48) where pure fibers, achieved by proteolytic digestion of S. mutans amyloid-containing mats, are likely only seen in laboratory settings. It has also been shown that the addition of monomeric protein to purified fibrils shifts the morphology of fibrils back to mats (48).…”
Section: Discussionmentioning
confidence: 99%
“…Because S. mutans amyloid mats have been confirmed to exhibit the same characteristic X-ray fiber diffraction pattern as isolated amyloid fibers (48), and because glycosylation of Cnm has been shown to protect this protein from proteolytic degradation (41), the visualization of amyloid mats rather than fibers by TEM confirms the formation of amyloid by native glycosylated Cnm.…”
Section: Transmission Electron Microscopy Confirms That S Mutans Cnm and Its Variants Form Amyloidsmentioning
confidence: 94%
See 1 more Smart Citation
“…AgI/II fragments comprised of the C-domain are able to form the functional amyloid fibers in vitro (Tang et al, 2016;Barran-Berdon et al, 2020). Furthermore, AgI/II functional amyloids contribute to stabilization of S. mutans biofilms (Oli et al, 2012;Tang et al, 2016;Barran-Berdon et al, 2020). Together, this information suggests a critical role of AgI/II protein interactions for the stabilization of streptococcal communities, as well as in the formation of a structural foundation in biofilms that may be taken advantage of by other species.…”
Section: Adhesive Function Functional Amyloids and Auto-aggregationmentioning
confidence: 97%
“…These released fragments can interact with surface anchored AgI/II proteins, particularly through the V-domain of the surface anchored protein with either the V-or C-domains of the fragmented protein (Heim et al, 2015;Rego et al, 2016;Tang et al, 2016;Rivière et al, 2020). AgI/II fragments comprised of the C-domain are able to form the functional amyloid fibers in vitro (Tang et al, 2016;Barran-Berdon et al, 2020). Furthermore, AgI/II functional amyloids contribute to stabilization of S. mutans biofilms (Oli et al, 2012;Tang et al, 2016;Barran-Berdon et al, 2020).…”
Section: Adhesive Function Functional Amyloids and Auto-aggregationmentioning
confidence: 99%